2006
DOI: 10.1055/s-2006-925259
|View full text |Cite
|
Sign up to set email alerts
|

Judgement of the Quality of Bowel Preparation at Screening Flexible Sigmoidoscopy is Associated with Variability in Adenoma Detection Rates

Abstract: Endoscopists with a higher ADR are more likely to be critical of the quality of bowel preparation. Training in judgement processes such as non-acceptance of suboptimal bowel preparation is required in order to ensure universally high standards in screening procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 12 publications
1
55
2
8
Order By: Relevance
“…Completeness of baseline colonoscopy was unknown in only 14% of patients, but quality of bowel preparation was missing in 39% of patients and it is known that the reporting of the bowel preparation quality is subjective. 64 The 'unknown' category was retained in analyses to avoid the introduction of bias, with the assumption that it probably comprised a mixture of examinations with both suboptimal and good-quality bowel preparation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Completeness of baseline colonoscopy was unknown in only 14% of patients, but quality of bowel preparation was missing in 39% of patients and it is known that the reporting of the bowel preparation quality is subjective. 64 The 'unknown' category was retained in analyses to avoid the introduction of bias, with the assumption that it probably comprised a mixture of examinations with both suboptimal and good-quality bowel preparation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Inadequate bowel preparation makes the procedure technically more challenging and increases the risk of an incomplete study and of complications. [1][2][3]8,9] 3. Rate of complete colonoscopy.…”
Section: Quality Of Bowel Preparation the Asgementioning
confidence: 99%
“…Data from a recent study showed a good correlation between colon cleanliness and detection rate of adenomas [20]. So a sufficiently cleaned colon using standard preparation techniques is the conditio sine qua non of an informative endoscopy.…”
Section: The Patientmentioning
confidence: 99%